Financing Energy Efficiency, Part 1 : Revolving Funds - Aditya, Lukas (World Bank, Washington, DC, 2018)
Despite offering huge economic returns, implementing energy efficiency measures encounters widespread and systemic barriers. One solution is developing effective and scalable financing and implementation mechanisms. Energy Efficiency Revolving Funds (EERFs) provide financing and related services to its clients to facilitate their investment in energy efficiency projects. Such funds facilitate access to finance in the near term while paving the way for commercial financing in the medium to long term, particularly in the public sector.